AB0776 Examination of changes in the prognosis and prognostic factors of microscopic polyangitis in japan. (23rd January 2014) - Shoda, T.; Takeuchi, T.; Kotani, T.; Nagai, K.; Wakura, D.; Isoda, K.; Yoshida, S.; Hata, K.; Makino, S.; Hanafusa, T.
Abstract : Objectives: We investigated changes in the prognosis and prognostic factors with respect to remission induction therapy in patients with microscopic polyangitis (MPA). Methods: Among patients with antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) in whom remission was induced in our hospital between 1995 and 2010, the subjects were 60 who were regarded as having MPA according to the classification algorithm established by Watte et al. (2007) (1). We compared the prognosis during the remission induction period between two groups: patients in whom remission was induced between 1995 and 2004, and those in whom remission was induced between 2005 and 2010. In addition, we analyzed prognostic factors in the early phase of treatment. Results: The subjects consisted of 23 males and 37 females. The median age (IQR) was 71 years (range: 59 to 75 years). According to EUVAS' severity classification of AAV(2), the lesion type was evaluated as localized in 4 patients, early systemic in 7, systemic in 26, and severe/refractory in 23 (2 with cerebral hemorrhage, 2 with hemorrhage of the digestive tract, 1 with pancreatitis, 10 with diffuse pulmonary hemorrhage, and 2 who were positive for anti-basement-membrane antibody). Using the Kaplan-Meier life table method, the 180-day survival rate was estimated to be 79%. However, after 2004, it improved to 90%. When analyzing prognostic factors using Cox's proportional hazard model, there were significant differences in the BVAS score and rate of decrease in the ANCA level between survival and primary disease-related death groups. Conclusions: With respect to remission induction therapy for MPA, the prognosis after was more favorable than before 2004. When examining prognostic factors, the results suggest that BVAS-based assessment and control of the rate of decrease in the ANCA level are useful. References: Watts R, Lane S, Hanslik T, et al: Development and validation of a consensus methodology for the classification of the ANCA-associated vasculitides and polyarteritis nodosa for epidemiological studies. Ann Rheum Dis 2007; 66:222-227. Mukhtyar C, Guillevin L, Cid MC, et al: EULAR recommendations for the management of primary small and medium vessel vasculitis. Ann Rheum Dis 2009; 68: 310-317. Disclosure of Interest: None Declared